THE EFFECT OF LEVERAGE, SYSTEMATIC RISK, FIRM SIZE, GROWTH OPPORTUNITY AND ROA ON EARNING RESPONSE COEFFICIENT IN PHARMACEUTICAL COMPANIES ON THE INDONESIA STOCK EXCHANGE - Ferian; Chairil Akhyar; Rico Nur Ilham; M. Subhan (PT. Radja Intercontinental Publishing, 2023)
This study examines the effect of Leverage, Systematic Risk, Firm Size, Growth Opportunity, and ROA on the Earning Response Coefficient of Pharmaceutical Companies on the Indonesia Stock Exchange. The data used in this study are secondary data for 2019-2021. In sampling, the author uses a purposive sampling technique, namely the sampling method based on specific criteria. The sample in this study was 7 pharmaceutical companies conducted from the first Quarter of 2019 to Quarter 4 2021, so the number of observations in this study amounted to 84 observations using panel data regression analysis. Data is obtained from the publication of the Indonesia Stock Exchange. The results indicate that Leverage negatively and significantly affects Earning Response Coefficient of Pharmaceutical Companies on the Indonesia Stock Exchange, Systematic Risk negatively and significantly affects the Earning Response Coefficient of Pharmaceutical Companies on the Indonesia Stock Exchange, while Firm Size positively and significantly affects the Earning Response Coefficient of Pharmaceutical Companies on the Indonesia Stock Exchange. Growth Opportunity does not influence the Earning Response Coefficient of Pharmaceutical Companies on the Indonesia Stock Exchange, and ROA negatively and significantly affects the Earning Response Coefficient of Pharmaceutical Companies on the Indonesia Stock Exchange..